Direct cyclohexanone oxime synthesis via oxidation–oximization of cyclohexane with ammonium acetate. Issue 9 (8th January 2020) - Peng, Ling; Liu, Chan; Li, Na; Zhong, Wenzhou; Mao, Liqiu; Kirk, Steven Robert; Yin, Dulin
Abstract : One-step preparation of cyclohexanone oxime from cyclohexane and ammonium acetate. 13.6% cyclohexane conversion and 51% cyclohexanone oxime selectivity are achieved. Varieties of different ammonias as readily available starting materials. Abstract : An unexpected cascade reaction for oxidation–oximization of cyclohexane with ammonium acetate was developed for the first time to access cyclohexanone oxime with 50.7% selectivity (13.6% conversion). Tetrahedral Ti sites in Ni-containing hollow titanium silicalite can serve as bifunctional catalytic centers in the reaction. This methodology not only provides a direct approach to prepare cyclohexanone oxime, but also simplifies process chemistry. Various available nitrogen sources, such as ammonium salt and even ammonia can be used as starting materials.